The Helm Wind of Cross Fell - Veale, Lucy; Endfield, G.H. (Wiley, 2014)
Crossfell is the highest point along the 268-mile route of the Pennine Way, at 893 metres (Figure 1). The climate of the North Pennines is temperate, with a small area classified as subarctic (Manley, 1936). The hills generally receive more precipitation, stronger winds, and colder temperatures than the surrounding areas. They are also home to the Helm, England’s only named wind.